Antioxidant and antiproliferative activities of Malaysian sea cucumber, (Holothuria edulis Lesson), extracts - Althunibat, Osama Yousef; Hashim, Ridzwan; Bakhtiar, M. Taher; Mohd. Daud, Jamaludin; Ikeda, Masa-Aki (2009)
Sea cucumber is a marine invertebrate of the phylum Echinodermata and the class Holothuroidea that found on the sea floor worldwide. In Asia, many of sea cucumber species are considered as traditional food items and have been used in featment of numerous diseases such as eczema, arthritis and hypertension. Previous scientific studies have shown multiple biological activities of sea cucumber species as antinociceptive, antimicrobial and antifungal properties. This study was conducted to investigate the antioxidant and antiproliferative activities of aqueous and organic extracts from sea cucumber, Holothuria edulis. Two different free radical systems were used to evaluate antioxidant activity of H. edulis, stable radical l,l-diphenyl-2- picrylhydrazyl (DPPH.) and linoleic acid free radical mediated p-carotene bleaching. In addition, Folin-Ciocalteau reagent was used to determine the total phenolic content of the exfacts. The inhibitory effect of the exfacts on proliferation of MCF-7 (human breast adenocarcinoma) and TEI (Human esophageal squamous cell carcinoma) human cancer cell lines were demonstrated by 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Our data showed that the gallic acid equivalent (GAE) of the total phenolic content in aqueous extract (GAE : 7.33 mglg) is higher than an organic extact (GAE = 2.17 mglg). An aqueous extract also exhibited higher.antioxidant capacity by using DPPH assay (ICso = 2.04 mg/ml vs. 8.73 mlmL in organic extract), as well as by using p-carotene bleaching assay (Antioxidant Activity : 42.69 %o vs. 28.52 % in organic extract). On the other hand, an organic extact showed higher antiproliferative effect against MCF-7 and TEI cancer cells, giving ICso : 28.0 and 17.5 pdmL, respectively than aqueous extract, that gave ICso : 133.0 pilmL against MCF- '7 and76.0 pgmL against TEl. In conclusion, frndings of this study revealed that H. edulis as a promising source ofnatural antioxidants and anticancer products.